2014
DOI: 10.1155/2014/192093
|View full text |Cite
|
Sign up to set email alerts
|

Small Islets Transplantation Superiority to Large Ones: Implications from Islet Microcirculation and Revascularization

Abstract: Pancreatic islet transplantation is a promising therapy to regain glycemic control in diabetic patients. The selection of ideal grafts is the basis to guarantee short-term effectivity and longevity of the transplanted islets. Contradictory to the traditional notion, recent findings implied the superiority of small islets for better transplantation outcomes rather than the large and intact ones. However, the mechanisms remain to be elucidated. Recent evidences emphasized the major impact of microcirculation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
(56 reference statements)
4
20
0
Order By: Relevance
“…S5a). The results, which showed a significantly larger distribution of small islets in the recipient liver with good prognosis after transplantation, are consistent with previous reports that small islets contributed to the transplantation outcome and show that this phenomenon is similar in cynomolgus monkeys 36,40 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…S5a). The results, which showed a significantly larger distribution of small islets in the recipient liver with good prognosis after transplantation, are consistent with previous reports that small islets contributed to the transplantation outcome and show that this phenomenon is similar in cynomolgus monkeys 36,40 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the correlation between the islet size and the results of transplantation, in many studies, the ratio of insulin-expressing beta cell content of islets was higher in smaller islets 36,[41][42][43] . The results from the present study confirmed this finding.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…CD31 is a marker of the vascular endothelium (31). To investigate whether the SIS-MSC scaffold improves the microcirculation of islets, we performed an immunofluorescence analysis for CD31.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have found evidence that small islets have higher survival rates and superior function as compared with large islets, because small islets are able to effectively receive oxygen and nutrients through diffusion, even after they are deprived of their native vascular network . The transport of insulin also greatly relies on diffusion, and large islets are inferior due to central necrosis, whereas small islet cell clusters can successfully minimize diffusion barriers and maintain viability and function .…”
Section: Discussionmentioning
confidence: 99%